EFEKTIVITAS KRIM ANTIJERAWAT EKSTRAK METANOL DAUN PACAR AIR (Impatiens balsamina L.) - Abdurraafi' Maududi Dermawan; Liza Pratiwi; Indri Kusharyanti (Majalah Obat Tradisional, 2015)
Many studies have found that Impatiens balsamina leaves contain antibacterial activity. The present study was conducted to evaluate antiacne effect from cream of methanolic extract from leaves of Impatiens balsamina L. towards Propionibacterium acnes and Staphylococcus epidermidis, which concentration that gives the most effective antiacne and to evaluate physical and chemical properties of creams. The simplicia was extracted by soxhlet technique and using methanol as solvent. Kirby-Baeur diffusion method was used to measure the antibacterial activity. The extract was formulated in cream with concentration of 10%, 15% and 20%. Evaluation of physical and chemical properties was done by organoleptic testing, spreadability, adhesive force, pH and antibacterial effectiveness. Data was analyzed using R-Commander program 2.14.1 Version. Formula II which contained 15% extract showed the most effective inhibiton to the growth of bacteria. The evaluation of FII cream showed that the cream was homogen, the spreadability was 21,24 + 1,464cm2, adhesive force more than 60 minutes, and pH of 6,53 + 0,057.